Typhonium phuocbinhense sp. nov. (Araceae: Areae), a new species from central Vietnam - Nguyen, van Du; Toan, Le Chi; Nguyen, van Dinh; Ha, Minh Tam; Thi, van Anh Nguyen; Croat, Thomas (Phytotaxa, 2021)
Typhonium phuocbinhense has been described as a new species from central Vietnam. The plant grows on sand-soil in the gaps of rocks and the banks of stream line in the Phuoc Binh National Park of Ninh Thuan Province. The species is different from all other species in the genus. It is closest to T. varians from Thailand but differs from this species by having leaves not variegated, spathe tube brown and spathe lamina much narrower and staminodes folded 180o at apex. Beside that the species key of Typhonium in Vietnam and the species information of distribution, ecology, habitat and conservation are also introduced.